Relaxation Assisted by Gending Sriwijaya Music as an Effort to Reduce Social Anxiety in Students - Arizona ARIZONA; Fattah Hanurawan (Department of Guidance and Counseling, FIP, Undiksha, 2026)
Social anxiety among adolescents is a psychological problem that can hinder social interaction skills, reduce participation in academic activities, and negatively affect emotional development and psychological well-being. Increasing social demands, educational pressures, and the limited availability of culturally relevant intervention strategies have made social anxiety an important issue that requires effective and contextualized treatment approaches. This study aimed to analyze, evaluate, and examine the effectiveness of a relaxation technique assisted by Gending Sriwijaya traditional music in reducing social anxiety among adolescents. The study employed a quantitative approach using a pretest-posttest control group experimental design. The participants consisted of 14 students identified as having high levels of social anxiety and were assigned to experimental and control groups. Data were collected using an adapted version of the Social Anxiety Scale for Adolescents (SAS-A), which had undergone a validation process and was used to measure participants’ social anxiety levels before and after the intervention. Data analysis was conducted using the Wilcoxon signed-rank test to examine within-group changes and the Mann-Whitney U test to compare differences between groups. The findings indicated that the relaxation technique assisted by Gending Sriwijaya traditional music significantly reduced social anxiety among participants in the experimental group compared to those in the control group. These results suggest that the integration of traditional music into counseling services has the potential to serve as an effective culturally responsive intervention for promoting adolescent mental health. The study provides important implications for the development of innovative, contextual, and culturally based school counseling practices that address students’ psychological needs.